Overcoming the challenges amongst online sellers in the clothing industry - Baquir, Eric Jr. J., De Venecia, Jhoanna., Labrador, Mahzen Nixx M., Lapuz, Hedrix M., Ramintas, Carl Angelo A., Reyes, Anieka Annrose S., Suarez, Kyle Justin N. 4 0 16; 5
Abstract This research study explores the challenges faced by online sellers in the clothing industry in Manila and investigates the relationship between the level of challenges and approaches to overcoming the challenges as experienced by online sellers in the clothing Industry. The theory of planned behavior is used as its theoretical framework focusing on people who act rationally based on their attitudes, subjective norms, and perceived behavioral control. A quantitative approach is used to employ correlational research to provide converging evidence. The researchers employed a data collection method called harvested email and the target respondents were 30 online sellers in the clothing industry in Manila. The study focuses on four key challenges: competition, building trust, providing exceptional customer service, and managing logistics and shipping. Through an in-depth analysis, the study examines the level of challenges experienced by online sellers in relation to their approaches for overcoming these challenges. Specifically, the approaches considered are brand management, improving customer service, and enhancing inventory and delivery systems. The findings of the study reveal that Facebook (86.7%) is the most frequently used online platform by Online Sellers and there is a significant relationship between the level of challenges experienced by online sellers and the effectiveness of the approaches used to overcome these challenges. These results shed light on the intricate dynamics within the online clothing market and provide valuable insights for online sellers aiming to enhance their strategies for overcoming industry-specific challenges. Keywords: Online Sellers, Clothing Industry, Challenges, Approaches, Competition, Trust, Customer Service, Logistics, Brand Management, Inventory, Delivery
Business Research: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2